Defect-phase engineered NiTi-TiO2 enabling near-unity selective photocatalytic CO2-to-methanol conversion - Ruonan Wang; Mingjia Zhang; Jingjing Liu; Xu Wu; Shule Zhang; Qin Zhong; Jianfeng Yao (Nature Communications)
Abstract Scaling up methanol yields by artificial photosynthesis at a modest cost remains thermodynamically challenge. Designing concerted reaction sites to control intermediate evolution and stimulate proton-coupled electron transfer (PCET) is necessary. Here we show a nickel-titanium-based catalyst that achieves near-millimolar hourly methanol yields with 99.79% selectivity and a solar-to-chemical conversion efficiency of 2.23%. This catalyst is synthesized through one-step etching of NiTi-layered double hydroxide, which generates abundant unsaturated sites, along with the in-situ formation of amorphous TiO2. Revealed by in-situ characterizations, these defect-rich units effectively suppress the formation of undesirable carbonate while promoting the favorable *COOH intermediate. Furthermore, theoretical simulations confirm this *COOH boost facilitates the production of *CO and accelerates the PCET steps. This work significantly advances efficient methanol production by artificial photosynthesis and offers fundamental insights into controlling reaction pathways for renewable fuel synthesis.